2013
DOI: 10.1186/1756-3305-6-310
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities and symbionts in the hard tick Haemaphysalis longicornis (Acari: Ixodidae) from north China

Abstract: BackgroundClose relationships between ticks and microbial communities are important for tick fitness and pathogen colonization and transmission. Haemaphysalis longicornis, distributed widely in China, can carry and transmit various pathogens and pose serious damages to public health and economics. However, little is known about the broader array of microbial communities and symbionts in H. longicornis under natural conditions. In the present study, we investigated the composition of bacterial communities assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…In this study, we found microbial community of H . longicornis is consistent with previous findings that Proteobacteria is the most abundant phylum in tick species , with Coxiella showing the highest abundance . Researches have been suggested that female Amblyomma americanum and Rhipicephalus microplus ticks possessed higher relative abundance of Coxiella ‐like endosymbionts compared to male ticks .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found microbial community of H . longicornis is consistent with previous findings that Proteobacteria is the most abundant phylum in tick species , with Coxiella showing the highest abundance . Researches have been suggested that female Amblyomma americanum and Rhipicephalus microplus ticks possessed higher relative abundance of Coxiella ‐like endosymbionts compared to male ticks .…”
Section: Discussionsupporting
confidence: 92%
“…The CLS-Ht mainly infects the ovaries and the Malpighian tubes, which is consistent with the previous observation of Coxiella -like symbionts in R. sanguineus and R. turanicus ticks [18]. No tissue-specific infectivity was observed for RLS-Ht, a conclusion that is similar with the Rickettsia- like symbiont distribution in H. longicornis and D. silvarum found previously [4]. The coinfection of symbionts is common in ticks.…”
Section: Discussionsupporting
confidence: 91%
“…It has been ascribed a possible helper role in tick molting processes (Zchori-Fein and Bourtzis, 2011, Figure 3). Rickettsia -like symbionts have also been reported to infect hard ticks from several genera (Baldridge et al, 2004; Clay et al, 2008; Liu et al, 2013). One study reported that Rickettsia -infected Dermacentor variabilis have slightly greater motility than uninfected ticks, indirectly influencing disease risk (Kagemann and Clay, 2013).…”
Section: Tick-microbiome Interactionsmentioning
confidence: 99%